PENERAPAN SISTEM ANTRIAN PADA FASILITAS PELAYANAN PADA LOKET PENGAMBILAN OBAT DI PUSKESMAS CIGUDEG BOGOR JAWA BARAT - Eliyah Eli; Aden Aden; Dewi Purnama Sari (MathVisioN, 2021)
Waiting to get a service is something that we often see or experience in everyday life. The phenomenon is referred to as a queue, where the stage of the series of queuing phenomena starts from the arrival of customers, waiting to be served (the server is busy) and leaving the queue when when they have received service. This queue occurs because the arrival rate is faster than the available service rate. This causes less than the maximum service provided to customers. The place of research in this study is at the Cigudeg Public Health Center, Bogor, West Java, with the time of the study being carried out on March 25, 2021 – April 23, 2021. The object in this study is the prescription queue that occurs at the medicine collection counter. As for the purpose of this study is to find alternative solution is by using the queuing theory analysis method. As for the result of this study, it can be concluded that the queuing system used by the Cigudeg Public Health Center is a single channel single phase with a queuing model ( M/M/1 ) : (GD//), which means that there is only 1 server at the counter. Therefore, there are still frequent queues of prescriptions at the counter. After analysis and calculation using the queuing method, a queuing model ( M/M/2 ) : (GD//) is obtained where the optimum number of servers obtained is 2 servers.